THE REPUBLIC OF SRPSKA AFTER THE WAR IN UKRAINE: BETWEEN GUARANTEED RIGHTS, DISAPPEARANCE AND INDEPENDENCE - Kostić Šulejić, Marina; Marković, Nikola (Political Review, 2024)
The article identifies and analyses three main determinants that affect the position of the Republic of Srpska (RS) in Bosnia and Herzegovina (BH) before and after the beginning of the war in Ukraine in February 2022 to determine the conflictual potential of this position and possible outcomes. The main hypothesis is that, with the ongoing processes of EU and NATO integration, Kosovo’s unilateral independence, and the rise of global conflicts and polarization, relations in the BH became more unstable and radicalised. The possible outcomes that the authors consider are the preservation of the Dayton position of the RS in the BH, the disappearance of the RS as a separate entity in the BH, and, the independence of RS as a form of self-determination and a way to protect the sovereign rights of Serbs. The authors employed content and discourse analysis methods and a comparison of three determinants before and after February 2022. They conclude that, since the war in Ukraine, the position of RS is pushed toward “radical outcomes” – disappearance or independence - in the action-reaction mode, which are at the same time the most conflictual outcomes, and less toward the most desired one – the preservation of Dayton Agreement and guaranteed rights based on consociative democracy.
Keywords: Bosnia and Herzegovina; Republic of Srpska; Dayton Agreement; High Representative for BH; consociative democracy; Serbs; Serbia